1799, 1800, 1801, 1802, 1803, 1804 yıllarında Yeni Kıta’nın tün-gün eşitliği bölgelerine yolculuk - Humboldt, Alexander von, 1769-1859. (İstanbul)
2 cilt (1. c. lxx, 428 sayfa ; 2. c. sayfa [429]-1023, [1] sayfa)